AB0203 INTRAPLATELET ANGIOGENIC AND GROWTH FACTORS IN SYSTEMIC SCLEROSIS. (June 2019) - Robles, Bryan-Josué Flores; Sánchez, María-Alejandra; Bueno Cabrera, José Luís; Martín-Buitrago, Lucía Nuñez; Casado, Cristina Gómez; Mendoza, Juan Mulero; Godoy, Hilda; Pinillos, Valvanera; Labrador-Sánchez, Eztizen; López-Martín, Juan Antonio; Elena-Ibáñez, Angel; Merino-Meléndez, Leticia; et al.
Abstract : Background: Systemic sclerosis (SE) is a serious disease of the connective tissue characterized by dysfunction of the microcirculation. Angiogenesis is a complex process regulated by both angiogenic and angiostatic factors. Normally the functions of these factors are under an adequate balance, however, under certain conditions these factors can be induced initiating disorganized angiogenic phenomena. Objectives: For the first time, the levels of intraplatelet growth and angiogenic factors (normalized by platelet number and volumen) are described in patients with systemic sclerosis. Methods: We included 23 patients with systemic sclerosis (ACR/EULAR) and 16 controls. Patients underwent a platelet-apheresis to obtain platelet-rich plasma (PRP) and platelet-poor plasma (PPP). The samples were subjected to a freeze-thaw process to break the cell membranes and release the platelet content. Subsequently the various factors were measured (VEGF-α, PDGF ββ, HGF, FGF2, G-CSF, MCP-1, IL-1α, IL-1β, IL-8, IL-6, IL-13). Finally, the results were normalized according to the value of the plaquetocrit (number and volumen of platelets). We compared the levels in platelet-rich plasma and in platelet-poor plasma. A cut-off value p <0.05. Results: The mean age of the patients was 52 years ± 9.71, with a duration of the disease of 8 years, 74% were patients with limited SE, 70% of the patients had pulmonary involvement. Both patientes and controls, the TFG-β was 12 times more concentrated in PRP than in PPP (p <0.0001), IL-1b 13 times more (p <0.0001), IL-6 10 times more (p <0.0001), G-CSF 11 times more (p <0.0001), VEGF- α more concentrated (11.6 times) p <0.005. When the PRP of the patients with scleroderma was compared with the PRP of the controls, only differences were found in the VEGF concentrations, being decreased in the patients with scleroderma respect to controls (p <0.0001). Table 1 and 2 . Conclusion: The levels of VEGF-α (intraplatelet) are lower in patients with SE vrs controls (p <0.0001). The intraplatelet values of the growth and angiogenic factors are higher than the plasma (patients and controls), finally, the plasma levels of these factors are similar in patients compare with controls. In almost all studies until today the measured levels have been carried out in serum, which are not precise since, in serum, several cells and lysate residues can alter the values, therefore, quantification in plasma is important. The present work is the result of the doctoral thesis of the main author. Reference: [1] Choi JJ, et al. Elevated vascular endothelial growth factor in systemic sclerosis. J Rheumatol2003; 30: 1529-33. Acknowledgement: Patients and bank blood secretary. Disclosure of Interests: Bryan-Josué Flores Robles Grant/research support from: Transport and hotel, María-Alejandra Sánchez : None declared, José Luís Bueno cabrera : None declared, Lucía Nuñez Martín-Buitrago : None declared, Cristina Gómez Casado: None declared, Juan Mulero Mendoza: None declared, Hilda Godoy: None declared, Valvanera Pinillos: None declared, Eztizen Labrador-Sánchez: None declared, Juan Antonio López-Martín: None declared, Angel Elena-Ibáñez: None declared, Leticia Merino-Meléndez: None declared, José Luis Andréu Sánchez: None declared